Final Report Pilot Study on Water Use Efficiency for Upper Ganga Canal (Uttar Pradesh) - Planning Commission (Planning Commission, 2003)
The work of conducting the "Pilot Study on Water Use Efficiency of (i) Western Yamuna Canal (Haryana) and (ii) Upper Ganga Canal (U.P.)" was awarded to WAPCOS (I) Ltd. by the Planning Commission, Govt, of India vide their Letter No. 0-15012/94/2000-SER dt. 13.3.2001 and office order No. 0-15012/94/2Y-SER dt. 26.3.2001. The basic objective of the Pilot Study was to ascertain the percentage of the total releases of canal water at headworks, being gainfully utilized for raising of crops.
Planning Commission Government of India
Planning Commission Government of India